1993
DOI: 10.1111/j.1365-2842.1993.tb01624.x
|View full text |Cite
|
Sign up to set email alerts
|

Taurodontism and length of teeth in patients with oligodontia

Abstract: Taurodontism and a reduced tooth length are reported to occur in patients with oligondontia. The aim of this study was to evaluate the occurrence of these factors in Dutch patients with oligodontia. Panoramic radiographs of 117 patients with oligodontia and 91 controls were collected. Taurodontism of the mandibular first molars was recorded and the length of cuspids, bicuspids and first molars of the mandible were measured. In patients with oligodontia 28.9% showed taurodontism of one or two mandibular first m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 12 publications
6
57
1
6
Order By: Relevance
“…In western European subjects, the prevalence is estimated to be about 10% (20,21). Although taurodontism does not involve molar teeth exclusively (22), it is found to be significantly more prevalent in second maxillary molars than in other teeth (23).…”
mentioning
confidence: 99%
“…In western European subjects, the prevalence is estimated to be about 10% (20,21). Although taurodontism does not involve molar teeth exclusively (22), it is found to be significantly more prevalent in second maxillary molars than in other teeth (23).…”
mentioning
confidence: 99%
“…31 The association of taurodontism with hypodontia has been shown. Seow and Lai 14 reported a taurodontism frequency of 35% in persons with hypodontia, and Schalk-van der Weide et al 15 found a frequency of 29% in those with oligodontia; however, only lower molars were assessed. Results of a study by Arte et al, 8 confirmed findings of the association of taurodontism to hypodontia in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Taurodontism has been described together with congenitally missing teeth [13][14][15] and hypodontia in many syndromes, 16 in sex chromosome anomalies with extra X chromosomes, 17,18 and in persons with cleft lip and palate. 19 Other syndromes have also been reported to present with taurodontism: 18p11.3 deletion, 20 SmithMagenis syndrome, 21 Tricho-dento-osseous syndrome, [22][23][24][25] Klinefelter's syndrome, [26][27][28] Williams syndrome, 29 McCune-Albright syndrome, 30 Down syndrome, 31 and Ellis-van Creveld syndrome.…”
mentioning
confidence: 99%
“…One explanation considered was that congenitally missing teeth, except for hereditary cases, has a greater likelihood of occurrence when the dental germ is developed later than the surrounding tissues, thus reducing the space available for the tooth to develop [15]. Also, previous studies demonstrated a highly significant correlation between microdontia and advanced CMT of the permanent dentition [5,6,41]. Both of these suggestions agreed with Bolk's theory of terminal reduction [42] that reduction of the distal element of a tooth group occurs more frequently than in mesially placed teeth, due to the phylogenetic evolution of humans.…”
Section: Open Access Http://scidocorg/ijdosphpmentioning
confidence: 99%
“…This could be in form of hypodontia (agenesis of one to six teeth), oligodontia (absence of six or more teeth, excluding the third molar) or anodontia (complete failure of one or both dentitions to develop [2][3][4][5][6]. It could be an isolated trait, or could be syndromic with an underlying recognizable clinical syndrome [7].…”
Section: Introductionmentioning
confidence: 99%